(3GdQjGVjGJ GdMOjKI (B:s (3GdeLehYGJ hWQb GdYO,GdGNWGA,GdJhRjYGJ GdJcQGQjI GdOhGd hGdfgGjGJ hGdGSJeQGQ,GdGbJQGf GdGSj hGddhZGQJe (B/s - (3OGQ SdGeI, NdhO Ydjs ((3YeGf(B: s (3OGQ UaGA(B, s, 2008)
(3efP GdbOe hGdQjGVjGJ JYQa HCe GdYdhe hCWdbhG YdjgG CSeGA cKjQI eKd edcI GdYdhe hbjUQI GdYdhe Edi BNQg ef GdCSeGAGdJj JHQR OhQ GdQjGVjGJ hCgejJgG hCfWdGbG ef GdCgejI GdHGdZI dgPG GdYde GdPj jONd aj LejY efGMj GdMjGI hEf gPg GdeGOI gj eJJWdH CLHGQj deYXe GdJNUUGJ aj GdLGeYGJ hGdcdjGJ abO Ve gPG GdcJGH aj WjGJg aUh QFjSjI JfGhdJ GdehGVjY GdJGdjI (B: (3GdeLehYGJ hWQb GdYO(B.-(3GdGNWGA(B.-(3GdJhRjYGJ GdJcQGQjI(B.-(3GdOhGd hGdfgGjGJ hGdGSJeQGQ(B.-(3GdGbJQGf GdGSj hGddhZGQJe(B.-(3GdYdGbGJ hGdGbJQGfGJ(B.-(3GbJQGfGJ cJjQI GdMOhO(B.-(3JMhjdGJ dG HdGSs
(3jHdjhZQGajG U(B.295s
Keywords: (3GbJQGf GdGSjs; (3GbJQGf dhZGQJes; (3GdeLehYGJs; (3JhRjYGJ JcQGQjIs; hg(3QjGVjGJs